2001
DOI: 10.1007/s10238-001-8018-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in glycemic control and cardiovascular risk in primary care patients with type 2 diabetes in West Indies

Abstract: There are limited resources and facilities at primary care clinics in most developing countries. Medical professionals are often faced with the challenges of providing standard health care delivery in the absence of adequate resources. We aimed to evaluate the long-term glycemic control and risk of cardiovascular disease in multi-ethnic groups of diabetic patients attending primary care clinics in Trinidad. One hundred and ninety-one (127 females, 64 males, mean age 56.6 years) patients with type 2 diabetes (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…Although fasting hyperinsulinaemia and insulin resistance are constant pathogenic mechanism in type 2 diabetes(6,7), insulin resistance is also associated with age and obesity, and with long standing diabetes, continued tissue insulin resistance gives rise to lipid abnormalities such as hypertriglyceridaemia. The disproportionate cluster of cardiovascular risk factors (hypercholesterolaemia, obesity, hypertriglyceridaemia, hyperinsulinaemia, elevated LDL cholestesterol) around the female patients and patients of East Indian origin is consistent with previous reports in this population (27,28). It would appear that the higher CVD risk in females than males might be related to the higher prevalence of obesity in females than males (Tables 2 and 5), a finding previously reported in non-diabetic healthy African subjects (18).…”
Section: Poor Glycaemic Controlsupporting
confidence: 81%
See 1 more Smart Citation
“…Although fasting hyperinsulinaemia and insulin resistance are constant pathogenic mechanism in type 2 diabetes(6,7), insulin resistance is also associated with age and obesity, and with long standing diabetes, continued tissue insulin resistance gives rise to lipid abnormalities such as hypertriglyceridaemia. The disproportionate cluster of cardiovascular risk factors (hypercholesterolaemia, obesity, hypertriglyceridaemia, hyperinsulinaemia, elevated LDL cholestesterol) around the female patients and patients of East Indian origin is consistent with previous reports in this population (27,28). It would appear that the higher CVD risk in females than males might be related to the higher prevalence of obesity in females than males (Tables 2 and 5), a finding previously reported in non-diabetic healthy African subjects (18).…”
Section: Poor Glycaemic Controlsupporting
confidence: 81%
“…values and reduced rates of complications than patients whose physicians set higher glycaemic goals (30). In conclusion, it is recognised that there is unequal gender and ethnic representation in the study, which is a reflection of the pattern of diabetes prevalence and general uptake in the primary care setting in this population (27,28). Again, although we assessed insulin sensitivity with a lessrecognised technical method, HOMA, results obtained with this method was comparable with other established techniques (31).…”
Section: Poor Glycaemic Controlmentioning
confidence: 67%
“…Although previous studies in this population have highlighted the greater risk of cardiovascular disease for this ethnic group [3][4][5]17], perhaps, due to their diet and glycaemic responses to foods [26]; this is the first report to indicate the levels of the risk in absolute terms. Our findings suggest that patients of Indian origin, irrespective of gender, were more vulnerable group and should be the first target for primary prevention of CHD.…”
Section: Discussionmentioning
confidence: 66%
“…While Tobago is comprised mainly of people of African descent, Trinidad has higher proportion of people of Indian origin [1]. Previous reports on cardiovascular disease risk in Trinidad have consistently shown that people of Indian origin had higher CVD risk factors than the other ethnic groups [3][4][5]17]. Similarly, studies in the United Kingdom [20] and North America [21,22] have confirmed higher risk of CHD amongst people of Asian origin than people of African descent.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation